ANALISIS JUAL BELI AKUN GAME ONLINE MOBILE LEGENDS PERSPEKTIF HUKUM EKONOMI ISLAM - Ahmad Burhanuddin; Sawaluddin Siregar; Zaianal Efendi Hasibuan (Adpertens: Jurnal Ekonomi dan Manajemen, 2025)
Mobile Legends Bang-Bang is a game released by a developer from China (moonton). Currently, The main problem in this research is how the sharia view of efforts to improve the community’s economy through the online game mobile legends based on a case study in the SIH Esports Gowa Community. The type of research in this paper uses qualitative data types, while the results of the research in rhis paper will describe the mechanism for economic improvement carried out by gamers based on sharia provisions. Based. Mobile Legends Bang-Bang is a game released by a developer from China (moonton). Currently, Mobile Legends has a managed to become a popular game with hundreds of million of users in more than 200 countries.. Initially game players who play only for entertainment and stress relief. The players themselves consider the game as a normal situation, now many gamers are making money from online games by becoming professional players, selling game account, and being a rank service jockey. The main problem in this research is how the sharia view of efforts to improve the community’s economy through the online game mobile legends based on a case study in the SIH Esports Gowa Community.